EFEKTIVITAS KEBIJAKAN FISKAL DAN KEBIJAKAN MONETER DALAM MENGATASI INFLASI DI INDONESIA PERIODE 1984-2019 - Rastri Paramita (Pusat Kajian Anggaran, 2021)
This research was conducted to determine the effectiveness of fiscal and monetary policy in dealing with inflation in Indonesia in the 1984-2019 period. The variables that serve as a proxy for fiscal policy are government spending (rBP) and tax revenue (rPP). Meanwhile, the proxies for monetary policy are the Indonesian interest rate (rSBI) and the exchange rate (rKurs). By using a quantitative methodology, VECM analysis tools is conducted because the variables are cointegrated but stationary in the first difference. The result of this study is the impulse response function (IRF) shows the shock of fiscal policy is responded more quicklyby inflation to achieve a level of stability than the shock given by monetary policy. Based on the results of the variance decomposition (VD) test, the rBP variable had the largest contribution of 89.15 percent to inflation. Meanwhile, rPP contributed 1.12 percent, RSBI contributed 0.01 percent, and rKurs contributed 8.21 percent to inflation. So that based on the results of the VECM test on the effectiveness of fiscal policy and monetary policy on inflation control for the 1984-2019 period, it is found that fiscal policy has greater effectiveness than monetary policy on controlling inflation.